1998
DOI: 10.4315/0362-028x-61.7.785
|View full text |Cite
|
Sign up to set email alerts
|

Application of Random Amplified Polymorphic DNA Analysis for Detection of Salmonella spp. in Foods

Abstract: The random amplified polymorphic DNA (RAPD) band patterns from 23 Salmonella spp. produced by use of an oligonucleotide primer (called du primer) designed on the basis of the N-terminal sequence of dulcitol 1-phosphate dehydrogenase (5'-GTGGTGACCCAGGATGGCCAGGTG-3') were different from those from 16 non-Salmonella spp. The bands at 460 and 700 bp were produced in all Salmonella strains tested. These RAPD fragments obtained from Salmonella typhimurium strongly hybridized with the corresponding RAPD bands from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…It is reported that the 23 Salmonella spp. tested in their work have all generated 2 fragments of 460 and 700 bp and that these fragments were unrelated to the dulcitol 1-phosphate dehydrogenase gene (Miyamoto et al, 1998). In this sense, the method is not entirely a gene-specific approach, and a single primer, as in the case of RAPD analysis, is used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the 23 Salmonella spp. tested in their work have all generated 2 fragments of 460 and 700 bp and that these fragments were unrelated to the dulcitol 1-phosphate dehydrogenase gene (Miyamoto et al, 1998). In this sense, the method is not entirely a gene-specific approach, and a single primer, as in the case of RAPD analysis, is used.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the large number of Salmonella serotypes, work toward finding DNA markers for general use in detecting Salmonella serotypes appears to be a challenge, especially when studies are based on methods that rely on the random amplification of DNA fragments. Thus, reports on the application of RAPD analysis for finding detection markers for Salmonella serotypes are rather limited (Miyamoto et al, 1998). Miyamoto et al (1998) have applied RAPD analysis for the detection of Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this technique may take as many as 4-5 days to confirm identity. More advanced methods for routine S. typhimurium detection include polymerase chain reaction (PCR) (Kumar et al, 2003;Peng and Shelef, 2001;Tseng et al, 1997), DNA hybridization (Meckes and MacDonald, 2003;Miyamoto et al, 1998;Nastasi et al, 1999), enzyme-linked immunosorbent assay (ELISA) (Tapchaisri et al, 1999) and biosensor-based assays (Kramer and Lim, 2004;Muhammad-Tahir and Alocilja, 2003;Olsen et al, 2003;Taitt et al, 2004) These modern methods offer many potential advantages for the rapid detection of microbial and viral pathogens in environmental samples and food in comparison with traditional long-term culture methods. Despite these advantages, their applications for real time detection and environmental monitoring remain in developmental stages with significant methodological hurdles.…”
Section: Salmonella Typhimurium {S Typhimurium) Ranks As a Leading Cmentioning
confidence: 99%
“…The resulting polymorphisms provide a simple means of constructing genetic maps and performing DNA fingerprinting. This method has been used to differentiate several species of microorganisms [2,15]. An AP-PCR using an 8-mer primer has been assayed for the differentiation of staphylococcal species isolated from meat and cheese [3].…”
Section: Introductionmentioning
confidence: 99%